Interleukin-6: Biology, signaling and strategies of blockade. Issue 5 (October 2015) - Schaper, Fred; Rose-John, Stefan
Highlights IL-6 signals through soluble and membrane-bound IL-6 receptors. Soluble IL-6 receptor and soluble gp130 buffer IL-6 in the blood. IL-6 activates JAK and Src kinases. IL-6 signaling is tighly regulated. Misregulated IL-6 action causes severe diseases. Strategies to block IL-6 action.